Linking Service Quality and Information Quality to Customer Loyalty: Evidence from B2B in Logistics Services - Samawea, Willyanoes; Setiyaningrum, Ari (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2026)
This study explores the influence of service quality and information quality on customer loyalty of B2B customers in logistics service company, with customer satisfaction and trust acting as mediating variables. A quantitative method was applied by collecting data from 278 business customers through structured questionnaires, which were analyzed using SEM-PLS. The findings reveal that service quality and information quality have both direct and trust-mediated effects on customer loyalty. Meanwhile, customer satisfaction does not mediate the influence of service quality or information quality on customer loyalty. These findings emphasize that improving service performance and ensuring reliable information are essential for sustaining long-term loyalty in business-to-business relationships.